Parotid Tumour Surgery- Personal Experience of 30 Cases - Islam, MB; Ahmed, I; Mortuza, MG; Sayeed, MA; Khanam, K; Das, Chinmoy Kanti (TAJ: Journal of Teachers Association, 2018)
Parotid gland is the most common site for salivery gland neoplasm. Most of the parotid tumours are benign and are commonly pleomorphic adenoma. Parotid tumours usually present with painless slow growing lobulated masses but may be associated with pain and paresis of the facial nerve if it is malignant. However it is difficult to differentiate clinically between benign and low grade malignant tumours. We studied thirty (30) patients with parotid gland tumours during Jan/2012 to April/2016 in dept. of surgery, Rajshahi Medical College Hospital. Twenty eight (28) were pleomorphic adenoma and two (2) were mucoepidermoid carcinoma. Superficial parotidectomy done in twenty five (25) patients and total parotidectomy done in five (5) patients. In all patients facial nerve dissection and preservation were performed safely without the facilities of nerve stimulator. Two years post operative follow up was satisfactory with no residual effect. This study highlights some of the important aspects in the management of the parotid gland tumours. TAJ 2013; 26: 57-60